Rehabilitation Programs for Female Recidivist Inmates: A Review at the Class IIA Women's Correctional Facility in Bandar Lampung - Zaky Syahputra Fawwas; Diah Gustiniati Maulani; Fristia Berdian Tamza; Dona Raisa Monica; Sri Riski (FOUNDAE (Foundation of Advanced Education), 2024)
The high rate of recidivism indicates that the rehabilitation programs available in correctional institutions have not been fully effective in assisting inmates with their rehabilitation and reducing the likelihood of reoffending after release. The Class IIA Women's Correctional Facility in Bandar Lampung is a specialized institution for female inmates, including those with a history of recidivism. This study aims to analyze the rehabilitation programs for female recidivist inmates at the Class IIA Women's Correctional Facility in Bandar Lampung and identify the challenges encountered in their implementation. A qualitative approach with a descriptive framework is employed to evaluate the rehabilitation programs at the institution in addressing female inmate recidivism. Data collection methods include interviews with prison staff, former inmates, and experts in the field of corrections, complemented by a literature review and direct observations. The findings reveal that while rehabilitation programs at the Class IIA Women's Correctional Facility in Bandar Lampung have an impact on inmates, they remain suboptimal. Vocational training programs are not sufficiently aligned with labor market demands, and psychological and social support services are limited, despite many inmates facing trauma and mental health issues. Societal stigma and a lack of family support further hinder reintegration efforts. To reduce recidivism and enhance reintegration, it is crucial to provide relevant vocational training, improve psychological services, and implement strategies to foster societal acceptance. Collaboration between the government, correctional institutions, and community organizations is essential in supporting former inmates and minimizing the risk of reoffending.